PERKEMBANGAN INDUSTRI RUMAHAN BAKSO IKAN MALINGPING DAN DAMPAKNYA TERHADAP SOSIAL EKONOMI MASYARAKAT KECAMATAN MALINGPING - Muh. Zulkarnaen; Rikza Fauzan; Arip Permana Putra (Desanta Publisher, 2024)
The fish ball home industry has emerged as a growing sector in Malingping District, prompting an in-depth examination of its development and socio-economic impact. Utilizing the historical method, encompassing heuristics, criticism, interpretation, and historiography, this study amalgamates oral and written sources through literature review, interviews, and documentation. The inception of the fish ball home industry in 1990 showed minimal impact, with a modest number of cottage industries initially established. However, over time, both the quantity and number of fish ball home industries burgeoned, significantly altering the socio-economic landscape of Malingping District. These changes reverberate across various facets of socio-economic life, including livelihoods, income, welfare, and education levels. Notably, the fish ball home industry has become a catalyst for job creation and entrepreneurial opportunities, fostering positive developments within the Malingping community.